EL GRITO DE MUNCH EN VERSOS LATINOAMERICANOS. - Hernández, Biviana (Revista Chilena de Literatura, 2025)
The article focuses on the interartistic relationship between Edvard Munch's painting "The Scream" and several Latin American poems that reinterpret it. Through ekphrasis, poets Miguel Ángel Zapata, Juan Manuel Roca, Ígor Barreto, José Watanabe, and Raúl Bueno explore the gap between the visual and the verbal, generating readings that transcend mere description of the artwork. Each poem offers a unique perspective on the human experience, violence, and the condition of the contemporary artist, revealing how poetry can engage in dialogue with painting to address social and emotional themes. The interaction between these artistic languages enriches the understanding of Munch's work and its relevance in current cultural contexts.